Analysis of Self-Financed Buy-Backs and Asset Exchanges. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
buy-backs of external debt financed by the debtor through asset sales generally result in unchanged or lower market prices for remaining debt. The contractual value of debt is reduced by some multiple of the market value of assets sold. The use of assets as collateral for new debt that is exchanged for old debt has effects equivalent to buy-backs financed by sales of the same assets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet